Conducta adictiva y su repercusión en la integración social en una persona privada de libertad - Palacios Villavicencio, Leonela Narcisa (2020)
In the present case study carried out in the center of deprivation of liberty in the city of Quevedo, we seek to identify addictive behaviors and how they influenced a social reintegration for a PPL, as well as obtaining information and applications of psychological techniques, such as observation, medical records, a battery of psychological tests, resulting in the diagnosis based on criteria in the ICD-10 manual, so that it describes how these behaviors intervened for a better emotional and social life of the subject. A therapeutic scheme based on cognitive behavioral therapy was tailored to the problem.